Outcomes of Differentiated Thyroid Cancer Patients Treated with Surgery and Radioactive Iodine at SQCCCRC - Omayma Elshafie; Abir Bou Khalil; Bushra Salman; Sofiullah Abubaker; Asiya Al-Busaidi; Khulood Al Riyami; Hassan Al-Sayegh; Juma Al Kasbi (Journal of Thyroid Cancer, 2026)
Objective To evaluate the treatment outcomes of patients with Differentiated thyroid cancer (DTC) who underwent total thyroidectomy followed by RAI therapy at the Sultan Qaboos Comprehensive Cancer Care and Research Centre (SQCCCRC) in Oman. Methods This is a retrospective observational clinical study conducted at SQCCCRC. The study included all patients diagnosed with DTC who were admitted to SQCCCRC between June 2021 and November 2023. A total of 255 patients were identified and met the inclusion criteria for this study. Results The mean age at diagnosis was 39.9 ± 12.4 years (range: 14–79), with 78% of patients being female. The mean BMI was 30.3 ± 6.4 kg/m², with nearly half of the cohort (48.2%) classified as obese (BMI ≥ 30). Most patients had papillary thyroid carcinoma (92.9%), while follicular and Hürthle cell carcinoma accounted for 5.9% and 0.8% of cases, respectively. Based on the American Joint Committee on Cancer (AJCC) staging, 86.3% of the patients were classified as stage I and 3.9% as stage II. Six patients (2.4%) had stage IVB disease. According to American Thyroid Association (ATA) risk stratification the majority were low-risk. Patient age was strongly associated with disease stage. The distribution of metastatic cases varied by region, with the highest proportion observed in Dhofar. Most patients (87.1%) received a single dose of radioactive iodine (RAI), with a median cumulative dose of 3.7 mCi). At six months post-treatment, 70.2% of patients had a TG level < 0.2 ng/mL. Conclusion The outcome of therapy in majority of our patients is favorable with 72% having excellent biochemical response at last follow up. None of the patients with distant metastasis achieved excellent response and a high proportion of them came from the Dhofar governorate, a targeted intervention would be of benefit. Low risk patients require special attention and may need radioactive iodine during follow up, unlike other regions and hence warrant very close follow up and further review to establish the best practice guidelines in our region.
Keywords: Differentiated thyroid cancer